The Role of Village Officials in Managing Social Conflict - Afrizal Tjoetra; Fazira Misla (Journal of Political and Governance Studies, 2025)
Background Social conflict in the Gampong Teungoh Iboh community, West Labuhan Haji District, South Aceh Regency occurs due to differences of opinion, misunderstandings, and interests between individuals and other community groups. The aim of this research is to find out the role of gampong officials in managing social conflict and to find out the obstacles faced by gampong officials in resolving social conflicts in Gampong Teungoh Iboh, West Labuhan Haji District, South Aceh Regency. The theories used in this research are conflict theory from Ralf Dahrendrorf and Miftah Thoha's role theory, namely to analyze social conflict problems in the Gampong Teungoh Iboh community. Methods This research uses a qualitative method with a descriptive approach and data collection techniques through observation, interviews and documentation. Results Based on the results of this research, it shows that gampong officials have not played a full role as mediators in resolving disputes in the community, so that gampong officials cannot realize the community's wishes to achieve peace with the disputing parties. Conclusions The obstacles faced by gampong officials in resolving disputes between the two conflicting parties, one of them did not attend the settlement hearing from the gampong officials. So this social conflict cannot be resolved until now.